2012
DOI: 10.1109/tsp.2011.2180901
|View full text |Cite
|
Sign up to set email alerts
|

Dirichlet Process Mixtures for Density Estimation in Dynamic Nonlinear Modeling: Application to GPS Positioning in Urban Canyons

Abstract: International audienceIn global positioning systems (GPS), classical localization algorithms assume, when the signal is received from the satellite in line-of-sight (LOS) environment, that the pseudorange error distribution is Gaussian. Such assumption is in some way very restrictive since a random error in the pseudorange measure with an unknown distribution form is always induced in constrained environments especially in urban canyons due to multipath/masking effects. In order to ensure high accuracy positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 44 publications
(78 reference statements)
0
34
0
Order By: Relevance
“…Finally, it must be emphasized that the spectral index α determines the estimation of parameters from geodetic time series and their uncertainties as well [27,25,11]. A recent study [28] shown that it also affects the estimation of real-time vehicles positions from Global Navigation Satellite System (GNSS) signals [28] (a different application of GNSS as presented here). These examples highlight the importance of estimating the spectral index and its uncertainty.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Finally, it must be emphasized that the spectral index α determines the estimation of parameters from geodetic time series and their uncertainties as well [27,25,11]. A recent study [28] shown that it also affects the estimation of real-time vehicles positions from Global Navigation Satellite System (GNSS) signals [28] (a different application of GNSS as presented here). These examples highlight the importance of estimating the spectral index and its uncertainty.…”
Section: Discussionmentioning
confidence: 93%
“…Though this might not be important for detrending in processes like case III, for example, geodetic time series, the non-Gaussianity behaviour of those parameters might still affect the estimates in other applications. [28] shown that classical localization methods are less efficient under multipath effects, than methods that estimate the error distribution. Histograms for marginalized likelihoods also provide information about crosscorrelation among parameters.…”
Section: Synthetic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A particular problem to be solved in this work is to estimate a probability density using a nonparametric Bayesian method involving an endless mix model as considered in [42] and [56]; but in the context of stochastic differential equations. We propose to use the following hierarchical structure to flexibly approximate the probability density of the solutions of the equation given in (1):…”
Section: Approximations Of the Solutions Of A Stochastic Differentialmentioning
confidence: 99%
“…However, these methods are computationally intensive, making a real time implementation very complicated. Finally, it is interesting to mention other techniques based on non-Gaussian error terms, such as Markov processes [12] or Dirichlet process mixtures [13].…”
Section: Introductionmentioning
confidence: 99%